2007
DOI: 10.1016/j.clinbiomech.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurement of subacromial space width during shoulder elevation: Technique and preliminary results in patients following unilateral rotator cuff repair

Abstract: Background: The shoulder's subacromial space is of significant clinical interest due to its association with rotator cuff disease. Previous studies have estimated the subacromial space width to be 2-17 mm, but no study has measured in-vivo subacromial space width during shoulder motion. The purpose of this study was to measure the in-vivo subacromial space width during shoulder elevation in patients following rotator cuff repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 41 publications
(45 reference statements)
7
78
3
2
Order By: Relevance
“…Moreover, measurement of the SAS at angles greater than 45° may not provide clinically relevant information because, above 35° to 40° of glenohumeral elevation, the supraspinatus tendon has likely already passed underneath the acromion and may no longer be at risk of impingement in the SAS. 4 Each ultrasound image was an individual measure. Prior to each ultrasound image, the subjects rolled their shoulders and moved about to change their posture, then were asked to assume the designated posture and reposition the arm in the appropriate arm angle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, measurement of the SAS at angles greater than 45° may not provide clinically relevant information because, above 35° to 40° of glenohumeral elevation, the supraspinatus tendon has likely already passed underneath the acromion and may no longer be at risk of impingement in the SAS. 4 Each ultrasound image was an individual measure. Prior to each ultrasound image, the subjects rolled their shoulders and moved about to change their posture, then were asked to assume the designated posture and reposition the arm in the appropriate arm angle.…”
Section: Methodsmentioning
confidence: 99%
“…However, evidence suggests that clinical relevance of measuring SAS at elevation angles greater than 35° to 40° of glenohumeral elevation may not be important, as the supraspinatus tendon has likely already passed underneath the acromion and thus may no longer be at risk of impingement in the SAS. 4 Measurements of the SAS and orientation of supraspinatus tendon found that, anatomically, the supraspinatus tendon was at greatest risk of impingement between the acromion and greater tuberosity of humerus between 27.7° to 36.1°. 4,5 The healthy group was not age and gender matched.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, less scapular UR appears to be a factor present at lower angles of arm elevation (below 90°) and in the scapular plane. In vivo biomechanical data 39 suggest that humeral elevations up to 90° but not beyond are positions where the rotator-cuff tendons lie directly beneath the anterior acromion and, therefore, are susceptible to extrinsic impingement. Above 90° of humeral elevation, the rotator-cuff tendons move medially and posteriorly and are no longer susceptible to mechanical impingement by the acromion.…”
Section: Angle Of Arm Elevationmentioning
confidence: 99%
“…The subjects in their study were older (mean  SD age, 63.2  10 years) than those in our sample (mean  SD age, 44.6  10 years) and had a diagnosis of a rotator cuff repair on the contralateral shoulder. Additionally, Bey et al 7 reported mean AHD values that were captured during dynamic arm elevation. We recognize that ultrasound-generated images capture only the outlet of the subacromial space and may not be able to capture the most inferior aspect of the undersurface of the anterior acromion or an osteophyte.…”
Section: Tablementioning
confidence: 99%